Assessing the impact of moon phase on the cutting of lapsed beech pollards. Issue 3 (3rd July 2018) - Read, Helen; Rubio, Samuel Álvarez; Wheater, C.P.; Garcia, Álvaro Sicilia
ABSTRACT: The charcoal makers in Navarra, Spain place great store in the importance of pruning trees in the correct moon phase. According to them, beech trees should be cut in a waxing/growing moon. A small group of lapsed beech pollards were cut back close to the bolling in either a waxing ( con luna ) or waning ( sin luna ) moon. Growth responses of the trees were studied after four and six growing seasons. Significant differences were found between the growth of trees in each treatment with, for example, branches on sin luna trees producing more new shoots, more clusters of shoots, having longer new shoots on retained branches and more callus. However, a difference between trees in each treatment was also found, with sin luna trees having significantly larger cut branch diameters. Larger stub diameters also resulted in fewer new shoots, shorter new shoots and greater amounts of dieback which makes interpretation of the results difficult in relation to moon phase.